The effect of hardaliye on reducing the formation of malondialdehyde during in vitro gastrointestinal digestion of meat products - Aksoy, Ayse Semra; Arici, Muhammet; Yaman, Mustafa (ELSEVIER, 2022)
Hardaliye is a non-alcoholic beverage produced from red/black grapes by adding mustard seeds and lactic acid fermentation. In this study, it was aimed to determine the total phenolic content (TPC) and total antioxidant capacity (TAC) of hardaliye samples produced with three different grape varieties (Shiraz, Merlot and Cabernet Sauvignon) before and after in vitro digestion, to determine their bioaccessibility, and to investigate their effects on reducing malondialdehyde (MDA) formation in meat products. TPC decreased after in vitro digestion in all three hardaliye samples and their bioaccessibility values were 57.64%, 41.54%, and 52.78% (for Shiraz, Merlot, and Cabernet Sauvignon hardaliye, respectively). After in vitro digestion TAC value according to the DPPH method increased in all samples and according to the CUPRAC method decreased in Merlot and Cabernet Sauvignon hardaliye samples, while it increased in the Shiraz hardaliye. After in vitro digestion, MDA value increased in control meat samples and decreased in the samples treated with hardaliye samples. Although treatment with other beverages was effective in reducing the post-digestion MDA value of some meat samples, the hardaliye samples were more effective in reducing this value and the lowest MDA bioaccessibility (%) values were determined in those treated with hardaliye samples. The samples with the lowest values were meat doner 1 treated with Shiraz hardaliye (10.27%); burger patties 2 treated with Shiraz hardaliye (22.40%); and meatball 2 treated with Cabernet Sauvignon hardaliye (7.12%). These findings indicate that hardaliye has potential beneficial health effects and can be used for the design of healthy eating patterns due to its lipid oxidation reducing potential in the gastrointestinal tract.
Keywords: Hardaliye; Antioxidant activity; Bioactive property; Bioaccessibility; In vitro digestion; Lipid peroxidation; Malondialdehyde; Grape; Oxidative stress; Nutrition; GRAPE SEED EXTRACT; LIPID-PEROXIDATION; NATURAL ANTIOXIDANTS; OXIDATIVE STABILITY; BIOACTIVE COMPOUNDS; PHENOLIC-COMPOUNDS; VITAMIN-C; POLYPHENOLS; Food Science & Technology